Covid-19: The role of infection control in protecting the healthcare workers in Vietnam - Binh, Tran Dinh; Loan, Tran Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Protecting healthcare workers (HCWs) is a top priority in COVID-19 pandemic at this time. HCWs who carry the pathogens will increase the risk of infecting their patients, their colleagues as well as the community. Therefore, HCWs must follow the guidance of preventive measures issued by the Ministry of Health to ensure safety, although that means they have to work under uncomfortable condition. That is the reason why the role of surveillance and assessment the risk of infection is extremely critical. Only with regular and continuous supervision, with instructions and reminders, can HCWs effectively prevent the COVID-19 infection, especially while being under intensity - work pressure of the current situation.